Learning style preferences in ESL classroom among form 2 students of Sekolah Menengah Jenis Kebangsaan Yok Bin, Melaka / Nadia Nur Afiqah Ismail - Ismail, Nadia Nur Afiqah (2011)
The study was conducted to identify the learning style preferences among Form 2 students of SMJK Yok Bin, Melaka in ESL classroom as well as to identify the differences between the learning style preferences of male and female students. A total of 150 students comprised of 75 male students and 75 female students were involved in this study. The Perceptual Learning Style Preferences Questionnaire (PLSPQ) which was developed by (Reid, 1987) has been used as the instrument of the study. The data analyzed using SPSS. The findings revealed that the major learning style preferences of the students were Group and Auditory learning style. However, they also favored Kinesthetic, Tactile, Visual, and Individual learning style as their minor learning style preferences. Moreover, the findings also revealed that there were no significance differences at α = 0.05 between Group, Auditory, Kinesthetic, Tactile, as well as Visual learning style due to gender differences. However, there was a significant difference at α = 0.05 for Individual learning style due to gender differences.